Development of BIPA Learning Media Based on Android Grammar Colored Blocks Foreign Students at Semarang State University Advanced Level - Khasanah, Fika Aulia; Istanti, Wati (LPPM Universitas Pekalongan, 2025)
The development of learning media is a major aspect to improve the achievement of learning competencies that are in accordance with the needs of Indonesian Language learners for Foreign Speakers (BIPA). At Semarang University, BIPA learning media containing grammar based on Android is still lacking. Therefore, the researcher developed BANATABA (Grammar Colored Blocks) learning media. BANATABA is an Android-based BIPA learning media that aims to teach Indonesian grammar to foreign students at Semarang State University at an advanced level. This development research uses the Sugiyono model, this research stage is summarized into five stages that are carried out systematically, because this stage is adjusted to the level of need, including: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, and ( 5) design revision . The results of the assessment by media experts showed that the BANATABA learning media obtained a feasibility percentage of 91%. Meanwhile, the results of the assessment by material experts showed that the BANATABA learning media obtained a feasibility percentage of 69%. The assessment by BIPA experts showed that the BANATABA learning media obtained a feasibility percentage of 95%. This research has theoretical and practical benefits, namely to teach Indonesian grammar through a digital platform and to motivate further research.